Improving the thermostatic steam trap characteristics using spring elements with the shape memory effect - Pylypchak, Vitaliy; Epifanov, Oleksandr; Patsurkovskyi, Pavlo; Shapovalov, Yuriy (Eastern-European Journal of Enterprise Technologies, 2024)
The object of research is the deformation-force characteristics of spring elements of thermostatic steam traps with the shape memory effect. The research solves the problem related to the imperfection of the design of steam traps controlling elements and their high inertia. Experimental studies on the impact of the spring force elements cooling rate on the deformation-force characteristics were conducted. Experimental studies showed that the significant impact of the spring force elements cooling rate on the deformation-force characteristics is observed exceptionally under the deformation mode at a temperature t ≤ Мf. Based on the results of the experiments, it was found that decreasing the cooling rate from 66.7 to 0.013 °C/s has a positive effect on the spring element deformation-force characteristics. Distinctive feature of the work is the study of winding pitch and thermal force cycling impact on the deformation-force characteristics of spring elements. It was found that using thermal force cycling makes it possible to reduce the force required for complete compression of the spring element by 60 %. Intensive decrease in the force required for the complete compression of the spring elements occurs during the first 100 thermal force cycles. The rational method for spring elements heat treatment has been given. It is based on the next steps: heating to a temperature of 400–500 °C for 1 hour; exposure at this temperature for an hour; cooling with rate 0.013 °C/s, the number of thermal force cycles is at least 100 with a winding pitch of 8·10–3 m. Based on research results, an improved design of thermostatic steam trap with controlling element in the form of cylindrical compression spring made of the VSP-1 alloy based on nitinol has been presented